Intentional Training With Speech Production Supports Children’s Learning the Meanings of Foreign Words: A Comparison of Four Learning Tasks - Junttila, Katja; Ylinen, Sari (Frontiers in Psychology, 2020)
To determine the best techniques to teach children foreign words, we compared the effectiveness of four different learning tasks on their foreign-word learning (i.e., learning word forms and word meanings). The tasks included incidental learning, intentional learning with production, intentional learning without production, and cross-situational statistical learning. We also analyzed whether children’s age and cognitive skills correlate with the learning of word forms and word meanings. Forty-four 5–8-year-old children participated in the study. The results reveal that the children were able to learn the correct word forms from all four tasks and no differences emerged between the effectiveness of the tasks on the learning of word-forms. The children also learned the word meanings with all four tasks, yet the intentional task with production was more effective than the incidental task. This suggests that the ability of children to learn foreign words benefited from them knowing that they were supposed to learn new words and producing them aloud while training. The age of the children correlated with their learning results for word forms and meanings on the intentional task without production. The older children learned more effectively than the younger children in this task. Children’s phonological processing skills were correlated with learning the word meanings from the incidental task, suggesting that children with better phonological skills were able to benefit from incidental learning more than children with poorer phonological skills. Altogether, the results suggest that children’s foreign-language learning benefits from intentional training with speech production regardless of their age or cognitive skills.